Rheumatoid arthritis in black Americans (1994)
Recently, MacGregor and colleagues' have reported a low prevalence of rheumatoid arthritis (RA) in black Caribbeans compared with white patients in inner city Manchester. Although clinical features of RA were similar in both groups, the small number of subjects precluded detailed comparison. Similar studies in black Americans are scanty. L6pezMendez et al2 observed no significant clinical differences between black and white Americans with regard to frequency of extraarticular manifestations (EAM), disability, fatality rate, and functional outcome.